Unveiling Urban Voices: Citizen Reporter Impact on Public Services Responsiveness in Makassar City - Hendrarso, Panji; Handoko, Pryo; Solihin, Ihin; Kurnia, Nina; Tania, Reni (Universitas Padjadjaran, 2024)
This study proposes to analyze the influence of netizen (net citizen) accounts on the government's response to public service issues in Makassar over one year. The research method involves using data collected from the user's accounts, focusing on the frequency of reporting, types of issues reported, geographic distribution of reports, types of media used, and government responses to these reports. The analysis indicates that reports through citizen reporter accounts tend to receive quicker responses compared to direct complaints, with respondents evaluating the quality of these responses more positively. These findings suggest that digital platforms, such as social media, are effective in enhancing responsiveness due to emergency events, public priorities, and social pressures resulting from viral reporting.